Antimicrobial susceptibility profiles of invasive bacterial infections among children from low- and middle-income countries in the Western Pacific Region (WPRO) – a systematic review and meta-analysisResearch in context - Nerida Moore; Elizabeth A. Ashley; Benjamin F.R. Dickson; Anousone Douangnouvong; Pathana Panyaviseth; Paul Turner; Phoebe C.M. Williams (The Lancet Regional Health. Western Pacific, 2024)
Summary: Background: Antimicrobial resistance increasingly impacts paediatric mortality, particularly in resource-constrained settings. We aimed to evaluate the susceptibility profiles of bacteria causing infections in children from the Western Pacific region. Methods: We conducted a systematic review and meta-analysis of bacteria responsible for common infections in children. We included studies published from January 2011 to December 2023 (PROSPERO CRD42021248722). Pooled susceptibilities were evaluated against empiric antibiotics recommended to treat common clinical syndromes. Findings: Fifty-one papers met inclusion criteria, incorporating 18,330 bacterial isolates. Of available published data, only six countries from the region were represented. Escherichia coli revealed a pooled susceptibility to ampicillin of 17% (95% CI 12–23%, n = 3292), gentamicin 63% (95% CI 59–67%, n = 3956), and third-generation cephalosporins 59% (95% CI 49–69%, n = 3585). Susceptibility of Klebsiella spp. to gentamicin was 71% (95% CI 61–80%, n = 2323), third-generation cephalosporins 35% (95% CI 22–49%, n = 2076), and carbapenems 89% (95% CI 78–97%, n = 2080). Pooled susceptibility of Staphylococcus aureus to flucloxacillin was 72% (95% CI 58–83%, n = 1666), and susceptibility of Streptococcus pneumoniae meningitis isolates to ampicillin was 26% (95% CI 11–44%, n = 375), and 63% (95% CI 40–84%, n = 246) to third-generation cephalosporins. Interpretation: The burden of antimicrobial resistance among bacteria responsible for common infections in children across the Western Pacific region is significant, and the currently recommended World Health Organization antibiotics to treat these infections may be inefficacious. Strategies to improve the availability of high-quality data to understand the burden of antimicrobial resistance in the region are necessary. Funding: The study was supported by an Australian Government National Health and Medical Research Council Investigator Grant. This research was funded in part by the Wellcome Trust [220211/Z/20/Z]. For the purpose of Open Access, the author has applied a CC BY public copyright licence to any Author Accepted Manuscript version arising from this submission.